Behavioural phenotype of Cornelia de Lange syndrome. Issue 4 (1st October 1999) - Berney, T P; Ireland, M; Burn, J
Abstract : A postal questionnaire was used to study 49 individuals with Cornelia de Lange syndrome (including both the classical and the mild forms) to ascertain behavioural phenotype. Ages ranged from early childhood to adulthood (mean age, 10.2 years; SD, 7.8) and the degree of mental retardation from borderline (10%), through mild (8%), moderate (18%), and severe (20%) to profound (43%). A wide variety of symptoms occurred frequently, notably hyperactivity (40%), self injury (44%), daily aggression (49%), and sleep disturbance (55%). These correlated closely with the presence of an autistic like syndrome and with the degree of mental retardation. The frequency and severity of disturbance, continuing beyond childhood, is important when planning the amount and duration of support required by parents.